1978
DOI: 10.1099/00221287-104-1-37
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Resistance to Superoxide, Low pH and Hydrogen Peroxide among Strains of Mycobacterium tuberculosis

Abstract: Six strains of Mycobacterium tuberculosis of different virulence in guinea-pigs were compared with regard to their resistance to low pH, to hydrogen peroxide (H202) at different pH values and to superoxide (-O,-). Low virulence was associated with susceptibility to H202 in native and isoniazid-resistant strains but not in laboratory-attenuated strain ~3 7~a . H,Oz resistance was only partly related to catalase content. Low virulence was not associated with susceptibility to an acid environment but the tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 31 publications
7
104
0
Order By: Relevance
“…We have also shown that catalase-negative strains of M . tuberculosis are killed in similar circumstances whereas catalasepositive strains are capable of survival, thus confirming the more extensive work of Jackett et al (1978). The implication is that M .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have also shown that catalase-negative strains of M . tuberculosis are killed in similar circumstances whereas catalasepositive strains are capable of survival, thus confirming the more extensive work of Jackett et al (1978). The implication is that M .…”
Section: Discussionsupporting
confidence: 71%
“…The concentration was chosen on the basis of a previous study on the susceptibility of M . tuberculosis to H202 (Jackett, Aber and Lowrie, 1978). Suspensions were incubated at 37"C, and at appropriate intervals samples of these suspensions were removed and viable counts were made.…”
Section: Methodsmentioning
confidence: 99%
“…superoxide-generating system was tested (Jackett et al, 1978a). Only the peroxidesusceptible strains of tubercle bacilli were killed by products of this system ( fig.…”
Section: B Lowriementioning
confidence: 99%
“…To survive inside macrophages, M. tuberculosis must withstand reactive oxygen species (ROS) 2 produced by phagocyte oxidase (NOX2/gp91 phox ) and reactive nitrogen species (RNS) produced by inducible nitric-oxide synthase in the macrophage (2). The bacterium is aided by several antioxidant defenses including a thick cell wall rich in lipoarabinomannan, cyclopropanated mycolic acid, and phenolic glycolipid I (PGL-1) (3), millimolar concentration of mycothiol (4,5), protective enzymes such as catalase (KatG) (6), superoxide dismutases (SodA and SodC) (7,8), peroxidase and peroxynitrite reductase complex (AhpC, AhpD, SucB, and Lpd) (9,10), and DNA-binding proteins such as Lrs2 (11), as well as an arsenal of exported proteins (12). However, little is known of transcriptional regulators sensitive to oxidation in M. tuberculosis that control these cellular defenses.…”
mentioning
confidence: 99%